2015
DOI: 10.1534/genetics.114.170514
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Studying Histone H1 Function in Vivo

Abstract: In this report, we investigate the mechanisms that regulate Drosophila histone H1 expression and its association with chromatin in vivo. We show that histone H1 is subject to negative autoregulation and exploit this result to examine the effects of mutations of the main phosphorylation site of histone H1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Instead, prior functional studies of H1 relies on RNAi knock-down or overexpression approaches. It has been shown that H1 is important for the maintenance of heterochromatin stability and gene expression (Ni et al 2006;Lu et al 2009Lu et al , 2013Vujatovic et al 2012), the S e p t e m b e r 4 , 2 0 1 9 5 regulation of DNA replication in polyploid cells (Andreyeva et al 2017), the compaction of chromatin in endo-replicating cells (Corona et al 2007;Lu et al 2009;Siriaco et al 2015), and stem cell maintenance in testis (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, prior functional studies of H1 relies on RNAi knock-down or overexpression approaches. It has been shown that H1 is important for the maintenance of heterochromatin stability and gene expression (Ni et al 2006;Lu et al 2009Lu et al , 2013Vujatovic et al 2012), the S e p t e m b e r 4 , 2 0 1 9 5 regulation of DNA replication in polyploid cells (Andreyeva et al 2017), the compaction of chromatin in endo-replicating cells (Corona et al 2007;Lu et al 2009;Siriaco et al 2015), and stem cell maintenance in testis (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%